A Grid as Smart as the Internet. (July 2020) - Liu, Yanli; Yu, Yixin; Gao, Ning; Wu, Felix
Abstract: A new era of electricity is dawning that combines the decarbonization of the grid with the extensive electrification of all sectors of society. A grid as smart as the internet is needed to harness the full potential of renewables, accommodate technology disruptions, embrace the rise of prosumers, and seamlessly integrate nano-, mini-, and micro-grids. The internet is built upon a layered architecture that facilitates technology innovations, and its intelligence is distributed throughout a hierarchy of networks. Fundamental differences between data flows and power flows are examined. The current operating paradigm of the grid is based on the conviction that a centralized grid operator is necessary to maintain instantaneous power balance on the grid. A new distributed paradigm can be realized by distributing this responsibility to sub-grids and requiring each sub-grid to maintain its net power balance. A grid as smart as the internet based on this new paradigm, as well as a hierarchical network structure and a layered architecture of operating principles, is presented.